2006
DOI: 10.1002/mame.200600083
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Hybrid Chitosan/Acrylic Resin Emulsions and Their Films

Abstract: Summary: Solutions containing chitosan of different molecular weights and several acidic monomers were prepared under various aging conditions. Hybrid chitosan/acrylic resin emulsions were prepared from these solutions by emulsion polymerization. The viscosities of the hybrid chitosan/acrylic resin emulsions were influenced significantly by the molecular weight of chitosan, the acidic monomer used, and the aging conditions. DSC and FT‐IR spectroscopy of the hybrid chitosan/acrylic resin films indicated that ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In our previous paper,7 we reported on the properties of hybrid chitosan/acrylic resin emulsions prepared using chitosan‐acidic monomer solution. In this work, to incorporate a q ‐chitosan into acrylic resin films, two types of acrylic resin emulsion were prepared, one with and one without a keto group.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous paper,7 we reported on the properties of hybrid chitosan/acrylic resin emulsions prepared using chitosan‐acidic monomer solution. In this work, to incorporate a q ‐chitosan into acrylic resin films, two types of acrylic resin emulsion were prepared, one with and one without a keto group.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the use of chitosan has been reported in a variety of fields 8–19. Furthermore, we demonstrated that hybridized chitosan/acrylic resin films have excellent adsorption ability for formaldehyde 6,7…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations